CLOUD TECHNOLOGIES AND THE INTERNET OF THINGS (IOT): THE INTERACTION BETWEEN CLOUD SERVICES AND CONNECTED DEVICES IN THE INTERNET OF THINGS - LEPETUN, MYKHAILO; PEREPELYTSIA, ARTEM; BATAIEV, SERGII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The gradual development of information and digital technologies has expanded the possibilities of intelligent data transfer, which is now widely used to solve everyday problems. Among these technologies is the acquisition and processing of data from IoT devices, which may contain a large amount of data to be stored in a cloud database, raising concerns about security and delays in processing requests for data. To this end, it is necessary to analyse the main differences between cloud computing and the capabilities of IoT devices. The study focuses on the interaction between cloud computing and connected devices of the Internet of Things. The author analyses the role of cloud platforms in ensuring efficient processing and storage of a large amount of data collected from connected devices. In accordance with the purpose of this study, a comparative analysis of the general characteristics of two technologies - cloud computing and the Internet of Things - was carried out in order to establish the relationship between cloud platforms and connected devices, with the aim of identifying the main advantages and disadvantages for an integrated system. The analysis provided insight into how cloud computing combined with IoT devices can complement each other through common elements such as the nature of interaction, connectivity, big data processing capabilities, and storage capabilities. The study considers the possibility of combining cloud computing with IoT devices on the example of an integrated system using different platforms in the cloud infrastructure to perform various requests and tasks. Analyzed according to the results of the integrated cloud computing system with IoT devices the possibility of improving the relationship, which will improve the processing of large amounts of data and increase the level of cyber defense through the use of cloud platforms and frameworks.